Meta-analysis on Brain Representation of Experimental Dental Pain. (February 2014) - Lin, C.-S.; Niddam, D.M.; Hsu, M.-L.
Functional magnetic resonance imaging (fMRI) has been widely used for investigating the brain representation associated with dental pain evoked by pulpal electrical stimulation. However, because of the heterogeneity of experimental designs and the small sample size of individual studies, the common brain representation regarding dental pain has remained elusive. We used imaging meta-analysis to investigate six dental pain-related fMRI studies (n = 87) and tested 3 hypotheses: (1) Dental pain is associated with the 'core' pain-related network; (2) pain-related brain activation is somatotopically organized in the somatosensory cortex; and (3) dental pain is associated with the cognitive-affective network related to pain. Qualitative and quantitative meta-analyses revealed: (1) common activation of the core pain-related network, including the somatosensory cortex, the insula, and the cingulate cortex; (2) inconsistency in somatotopically organized activation of the primary somatosensory cortex; and (3) common activation in the dorsolateral prefrontal cortex, suggesting a role of re-appraisal and coping in the experience of dental pain. In conclusion, fMRI combined with pulpal stimulation can effectively evoke activity in the pain-related network. The dental pain-related brain representation disclosed the mechanisms of how sensory and cognitive-affective factors shape dental pain, which will help in the development of more effective customized methods for central pain control.